Day 15 and Day 33 Minimal Residual Disease Assessment for Acute Lymphoblastic Leukemia Patients Treated According to the BFM ALL IC 2009 Protocol: Single-Center Experience of 133 Cases - Radu, Letitia-Elena; Colita, Andrei; Pasca, Sergiu; Tomuleasa, Ciprian; Popa, Codruta; Serban, Catalin; Gheorghe, Anca; Serbanica, Andreea; Jercan, Cristina; Marcu, Andra; Bica, Ana; Teodorescu, Patric; et al. (Frontiers in Oncology, 2020)
Introduction: Childhood acute lymphoblastic leukemia (ALL) is a hematologic malignancy characterized by the acquisition of several genetic lesions in the lymphoid progenitors with subsequent proliferation advantage and lack of maturation. Along the years it has been repeatedly shown that minimal residual disease (MRD) plays an important role in prognosis and therapy choice. The aim of the current study was to determine the prognostic role of MRD in childhood ALL patients in conjunction with other relevant patient and disease characteristics, thus showing the real-life scenario of childhood ALL. Patients and Methods: The retrospective study includes childhood ALL patients that were treated according to the BFM ALL IC 2009 between January 2016 and December 2018 at the Fundeni Clinical Institute, Bucharest, Romania. Results: None of the variables significantly influenced the induction-related death in our study. None of the variables independently predicted relapse free survival (RFS), with the highest tendency for statistical significance being represented by poor prednisone response. Non-relapse mortality (NRM) was independently predicted by age, prednisone response and day 33 flow cytometry-MRD (FCM-MRD). Overall survival (OS) was independently predicted by prednisone response and day 33 FCM-MRD. Event free survival (EFS) was independently predicted by age, prednisone response and day 33 FCM-MRD. Conclusion: Prednisone response, day 15 FCM-MRD, day 33 FCM-MRD and the risk group represent the most important factors that in the current study independently predict childhood ALL prognosis.